2024
DOI: 10.1002/cam4.6923
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the SARS‐CoV‐2 pandemic on colorectal cancer diagnosis and prognosis

Lucía Medina‐Prado,
Noelia Sala‐Miquel,
Marta Aicart‐Ramos
et al.

Abstract: Background and Study AimsOur aim was to determine the impact of the SARS‐CoV‐2 pandemic on the diagnosis and prognosis of colorectal cancer (CRC).Patients and MethodsThis prospective cohort study included individuals diagnosed with CRC between March 13, 2019 and June 20, 2021 across 21 Spanish hospitals. Two time periods were compared: prepandemic (from March 13, 2019 to March 13, 2020) and pandemic (from March 14, 2020 to June 20, 2021, lockdown period and 1 year after lockdown).ResultsWe observed a 46.9% dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…A closer analysis of our patients with regard to restrictions during the lockdowns showed more initially advanced tumor stages during lockdowns (T4b: 27.3% vs. 6.2%), with a consecutive trend towards a higher proportion of neoadjuvant-treated patients compared to the control group ( Table 6 ). This is consistent with the observations of a Spanish group that found higher rates of stage IV colorectal cancer during the lockdown [ 39 ]. Other studies showed similar results at the beginning of the pandemic, comparable to our lockdown periods, with a trend towards higher tumor stages [ 40 , 41 , 42 ] and fewer early-stage cancers [ 10 ] during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 93%
“…A closer analysis of our patients with regard to restrictions during the lockdowns showed more initially advanced tumor stages during lockdowns (T4b: 27.3% vs. 6.2%), with a consecutive trend towards a higher proportion of neoadjuvant-treated patients compared to the control group ( Table 6 ). This is consistent with the observations of a Spanish group that found higher rates of stage IV colorectal cancer during the lockdown [ 39 ]. Other studies showed similar results at the beginning of the pandemic, comparable to our lockdown periods, with a trend towards higher tumor stages [ 40 , 41 , 42 ] and fewer early-stage cancers [ 10 ] during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 93%